2004
DOI: 10.1042/bj20031579
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome inhibitors up-regulate haem oxygenase-1 gene expression: requirement of p38 MAPK (mitogen-activated protein kinase) activation but not of NF-kappaB (nuclear factor kappaB) inhibition

Abstract: Regulation of intracellular protein stability by the ubiquitin-dependent proteasome system plays a crucial role in cell function. HO-1 (haem oxygenase) is a stress response protein, which confers cytoprotection against oxidative injury and provides a vital function in maintaining tissue homoeostasis. In the present study, we found a novel action of proteasome inhibitors MG132 and MG262 on HO-1 induction, and characterized the underlying mechanisms. MG132 (> or =0.1 microM) treatment resulted in a marked time- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 60 publications
3
35
0
Order By: Relevance
“…Furthermore, this paper also reported that PDTC, another NF-κB inhibitor, increases HO-1 expression. Like MG132, PDTC induces HO-1 expression via AP-1 signaling [45]. In our studies, Bay activates p38 MAPK signaling, but this signaling was not involved in Bay-induced HO-1 expression (Fig.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Furthermore, this paper also reported that PDTC, another NF-κB inhibitor, increases HO-1 expression. Like MG132, PDTC induces HO-1 expression via AP-1 signaling [45]. In our studies, Bay activates p38 MAPK signaling, but this signaling was not involved in Bay-induced HO-1 expression (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…Although these three NF-κB inhibitors use different mechanisms, all can efficiently inhibit NF-κB signaling. Recently, other group reported that MG132 induced HO-1 expression in Raw 264.7 macrophage cells [45]. Wu et al suggested that MG132 increases HO-1 expression through activation of p38 MAPK-AP-1 signaling and partial stabilization of HO-1 protein and that this phenomenon was independent of NF-κB signaling.…”
Section: Discussionmentioning
confidence: 98%
“…Pathway-To determine the role of FN-induced NF-B in cell attachment, Caco2-BBE cells were exposed to FN in the presence or absence of NF-B inhibitors MG-132 (29) or ADTC (30). As shown in Fig.…”
Section: Fn Mediates Cell Attachment Through Activation Of Nf-b Signamentioning
confidence: 99%
“…Therefore, oxidative stress could cause cell death via apoptotic pathways. Several studies have shown that oxidative stress is closely associated with the proteasome, as the proteasome is involved in regulating anti-oxidants, including catalase, heme oxygenase-1 (HO-1), copper/zinc-superoxide dismutase and γ-GCS [11][12][13][14] . However, the relationship between proteasome dysfunction and oxidative stress is still a matter of dispute.…”
Section: Introductionmentioning
confidence: 99%